Relationship knowledge and attitudes towards willingness to receive COVID-19 vaccination in NTB Province - Fidya Rizka; Kristiani Murti Kisid; Endy Bebasari Putri (International Journal of Health Science and Technology, 2021)
COVID-19 is one of the diseases with a very high and fast spread that requires vaccination as a protection step. The purpose of this study is to find out the relationship between knowledge and attitude towards willingness to receive COVID-19 vaccination in NTB Province. This research is an Observational research with cross sectional design. The results of this study were the majority of respondents with a level of knowledge (62.3%), good attitude (66%) willing to receive COVID-19 vaccination. The results of bivariate analysis resulted in a significant relationship between knowledge of COVID-19 vaccination and attitude towards willingness to receive COVID-19 vaccination.